2019
DOI: 10.1111/asj.13208
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐222 inhibits apoptosis in porcine follicular granulosa cells by targeting the THBS1 gene

Abstract: Apoptosis of granulosa cells affects follicular atresia and reproduction and is regulated by miRNAs and the expression of certain genes. For the present study, we investigated the regulatory relationship between microRNA‐222 (miR‐222) and THBS1 in porcine follicular granulosa cells (pGCs) and its effects on apoptosis to provide empirical data for developing methods to improve pig fecundity. Results revealed that miR‐222 promotes the proliferation of pGCs. MiRNA mimics and luciferase reporter assays revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 46 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…A previous study reported that THBS-1 inhibits angiogenesis and induces endothelial cell apoptosis [33]. Zhu et al demonstrated that miR-222 inhibits apoptosis in porcine follicular granulosa cells by suppressing the expression of THBS1 [34]. Based on previous studies and the current results, we postulate that cfa-let-7a suppresses cellular apoptosis by targeting THBS1, which would be beneficial for ORFV replication in GSF cells.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A previous study reported that THBS-1 inhibits angiogenesis and induces endothelial cell apoptosis [33]. Zhu et al demonstrated that miR-222 inhibits apoptosis in porcine follicular granulosa cells by suppressing the expression of THBS1 [34]. Based on previous studies and the current results, we postulate that cfa-let-7a suppresses cellular apoptosis by targeting THBS1, which would be beneficial for ORFV replication in GSF cells.…”
Section: Discussionsupporting
confidence: 71%
“…Overall, THBS1 was downregulated much more than other four cfa-let-7a targets based on the above results. Furthermore, previous studies reported that THBS1 was related to apoptosis [33,34] which was an important immune mechanism used by cells against viral infection. Therefore, we first selected THBS1 for Western blot analysis.…”
Section: Cfa-let-7a_r+2 Target Prediction and Validationmentioning
confidence: 99%
“…The final two granulosa subclusters can be identified as mitotic and atretic cells based on their expression of previously validated markers. Indeed, transcripts enriched in the latter are consistent with markers of atretic follicles including Caldesmon 1 (Cald1) (Hatzirodos et al 2014), Phosphoinositide-3-Kinase Interacting Protein 1(Pik3ip1) (Piersanti et al 2019), Thrombospondin 1 (Thbs1) (Thomas et al 2008; Garside et al 2010; Zhu et al 2019), and SRY-Box Transcription Factor 4 (Sox4) (Terenina et al 2017; Fan et al 2019). While markers found in mitotic granulosa cells are universally characteristic of dividing cells ( Table S5 ).…”
Section: Discussionmentioning
confidence: 90%
“…Higher expressions of CASP3 , one of the pro-apoptotic genes, induce the apoptosis of GCs in bovines [36]. Downregulation of the pro-apoptotic CASP3 gene inhibits the apoptosis of GCs in pigs [40]. The mRNA level of CASP3 in GCs is negatively associated with the number of preovulatory follicles in humans, indicating that the accumulation of CASP3 impairs the development of follicles [41].…”
Section: Discussionmentioning
confidence: 99%